Synthesis, characterization, and thermal study of solid-state alkaline earth metal mandelates, except beryllium and radium - Silva, R. C. [UNESP]; Caires, F. J. [UNESP]; Gomes, D. J. C. [UNESP]; Colman, T. A. D. [UNESP]; Ionashiro, Massao [UNESP] (Springer, 2014)
Characterization, thermal stability, and thermal decomposition of alkaline earth metal mandelates, M(C6H5CH(OH)CO2)(2), (M = Mg(II), Ca(II), Sr(II), and Ba(II)), were investigated employing simultaneous thermogravimetry and differential thermal analysis or differential scanning calorimetry, (TG-DTA or TG-DSC), infrared spectroscopy (FTIR), complexometry, and TG-DSC coupled to FTIR. All the compounds were obtained in the anhydrous state and the thermal decomposition occurs in three steps. The final residue up to 585 A degrees C (Mg), 720 A degrees C (Ca), and 945 A degrees C (Sr) is the respective oxide MgO, CaO, and SrO. For the barium compound the final residue up to 580 A degrees C is BaCO3, which is stable until 950 A degrees C and above this temperature the TG curve shows the beginning of the thermal decomposition of the barium carbonate. The results also provide information concerning the thermal behavior and identification of gaseous products evolved during the thermal decomposition of these compounds.
Keywords: Alkaline earth metals; Mandelate; Thermal behavior; TG-FTIR; Evolved gases